“Para encher os olhos”: identidades e representações culturais das rainhas e princesas do clube Treze de Maio de Santa Maria no jornal A Razão (1960-1980) - Escobar, Giane Vargas (2017)
The present thesis bridges questions regarding type, race and class, with the objective of carrying out a cultural analysis, at the centre of which are the queens and princesses of the beauty contests carried out by the Treze de Maio Club, in the city of Saint Maria, Rio Grande do Sul, in the decades of 1960, 1970 and 1980. This research is anchored in the theory of culture according to Raymond Williams – the cultural hypothesis of structures of feeling and three levels of the culture: lived culture, recorded culture and the culture of selective tradition in order to talk about the space given to these women in the social column of the newspaper A Razão, given that fact that it is a vehicle of communication that selects cultural traditions. Our investigation is carried out in the context of qualitative inquiry, with a theory and methodology based on what Williams called his "position": cultural materialism. Results of our analyses point toward the selection of a ―desirable femininity‖, in addition to the segregation between women from "downtown" and women from "the neighbourhood" as well as between black women and white women, thus showing the racist and segregationist hallmark of Santa Maria society and the newspaper A Razão. In an attempt to decolonize our thinking, our investigation includes theories offered by black intellectuals like Sueli Carneiro, Angela Davis, Kimberlé Crenshaw, Lélia Gonzalez, Bell Hooks and Neusa Santos Souza. This allowed to us to identify several forms of combined or mutually intercrossed oppression within the Black club and the wider Santa Maria society. Our study is also anchored in the concepts of identity and representation according to Stuart Hall. The Treze de Maio Club represented a second home and a place for the affirmation of the "race". It was there that these queens and princesses built friendships and secured lifelong commitments, romantic relationships, engagements and marriages, all in a constant, persistent incentive toward the reconstruction of the Black couple and the ideal Black family, the Treze de Maio family.